Post-traumatic, Depression, Anxiety, and Stress Symptoms among Malaysian Firefighters - Abdul Azis H; Zairina A. Rahman; Mohd Radzniwan A Rashid; Baharom N; Awang H; Mohammad Lukman NH; Zainal Abidin MZ (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2024)
Indexed by WOS/ Scopus